-3((b)^-2)+6=-6 I can find the answer on an online calculator but i would very much like to know how to do find b via step by step
$\displaystyle -3b^{-2}+6=-6$
Use SAMDEB (Subtraction/Addition, Multiplication/Division, Exponents, Brackets, Repeat if necessary after brackets removed)
In this case
$\displaystyle -3b^{-2}= -12$ subtract 6 on both sides
$\displaystyle b^{-2} = 4$ divide by -3 on both sides
$\displaystyle b^{2} = \frac{1}{4}$ Multiply both sides by b^{-2} and divide by 4
$\displaystyle b = \sqrt{\frac{1}{4}$ Take the square root on both sides (Exponents)
$\displaystyle b = \frac{1}{2}$ Recall the fact that since the square root is also a power (of $\displaystyle \frac{1}{2}$) and hence $\displaystyle \sqrt{\frac{a}{b}} = \frac{\sqrt{a}}{\sqrt{b}}$